"Early results after initiation of a rib fixation programme: A propensity score matched analysis". Issue 1 (January 2022) - Niziolek, Grace; Goodman, Michael D.; Makley, Amy; Millar, D Anderson; Heh, Victor; Pritts, Timothy A.; Janowak, Christopher
Highlights: Propensity-score match used to select non-operatively managed rib fractured patients to compare to operative patients. Early operative results show shortened time on ventilator and improved discharge to home. Further operative group maintains early improvements in addition to fewer respiratory complications. Improved protocol adherence increases frequency of operations. Abstract: Introduction: Chest wall injuries are very common in blunt trauma and development of treatment protocols can significantly improve outcomes. Surgical stabilisation of rib fractures (SSRF) is an adjunct for the most severe chest injuries and can be used as a part of a comprehensive approach to chest injuries care. We hypothesized that implementation of a SSRF programme program would result in improved short-term outcomes. Materials and methods: The characteristics of the initial group of SSRF patients (Early-SSRF ) were used to identify matching factors. Patients prior to SSRF protocol underwent a propensity score match, followed by screening for operative indications and contraindications. After exclusions, a non-operative (Non-Op ) cohort was defined (n=36) resulting in an approximately 1:1 match. An overall operative cohort, inclusive of Early-SSRF and all subsequent operative patients, was defined (All- SSRF ). A before-and-after analysis using chi-squared, Students T-tests, and Mann-Whitney U-tests were used to assess significance at the level of 0.05. Results: Early-SSRF (n=22) and All-SSRF (n=45) were compared to Non-Op (n=36). The selection process resulted in well matched groups, and equally well-balanced operative indications between the groups. The Early-SSRF group demonstrated shortened duration of mechanical ventilation and a decreased frequency of being discharged a long-term acute care hospital. The All-SSRF group again demonstrated markedly shorter duration of mechanical ventilation compared to Non-Op (median 6 days vs 16 days, p < 0.01), more decrease discharge to a long-term acute care hospital (9% vs. 36%, p=0.01), and reduced risk for tracheostomy (8.9% vs. 33.3% respectively, p<0.01) Conclusion: The introduction of an operative rib fixation to a comprehensive chest wall injury protocol can produce improvements in clinical outcomes that decrease time on the ventilator and tracheostomy rates, and result in more patients being discharged to home. Creation and implementation of a chest wall injury protocol to include SSRF requires a multidisciplinary approach and thoughtful patient selection.